The Relationship Between Renal Stones and Primary Aldosteronism - Chang, Chun-Kai; Chang, Chin-Chen; Wu, Vin-Cent; Geng, Jiun-Hung; Lee, Hsiang-Ying (Frontiers in Endocrinology, 2022)
Introduction The association between primary aldosteronism (PA) and nephrolithiasis is still unclear. The hypercalciuria and hypocitraturia of PA patients might be the reason lead to recurrent calcium nephrolithiasis. This study aimed to evaluate the relationship between PA and renal stones including stone size and density. Materials and Methods From November 2004 to March 2021, we included 610 patients who had hypertension history in our medical center retrospectively and all the enrolled patients have PA data survey. In total, 147 patients have kidney stone in our study. We divided into 44 patients with essential hypertension as group 1 and 103 patients with PA as group 2. Pearson χ2 test and independent Student’s t test were performed to examine the differences among variables. Results The mean age was 54.4±12.0 years in group 1 and 53.0±11.1 years in group 2. The incidence rate of renal stones in PA group is around 24%. There are also no significant different between two groups in gender, systolic/diastolic blood pressure, duration of hypertension, diabetes mellitus history, and laterality of kidney stone. However, the mean stone size was 4.0±3.3 mm in group 1 and 6.5±7.2 mm in group 2, a significant larger renal stone size was noted in PA group than in essential hypertension group (P=0.004). The HU density is higher in PA group than essential hypertension cohort although it did not reach significant difference (P=0.204). Conclusions Our study revealed that PA patients have higher incidence rate of renal stones. The PA related renal stones present larger and harder than essential hypertension group. Further investigation about the association between PA and renal stones is warrant.